Translation Strategy of Figure of Speech in Short Story - Maharani, Sang Ayu Isnu (Lingual Journal of Language and Culture; Vol 2 No 2 (2016), 2016)
This study is a descriptive qualitative study which concern with literary translation in a short story. It aimed at identifying figures of speech and also describing the strategies applied in translating figure of speech. The data was collected by library research method and note taking technique. The finding showed that the figure of speech found were mostly simile and one hyperbole. The strategies applied were retention of the similar vehicle, and retention of the same vehicle plus explication of similarity feature (s).
Keywords: figurative language, figure of speech, literary translation, short stories